1995
DOI: 10.1364/ol.20.000231
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in diffuse media with ultrafast degenerate optical parametric amplification

Abstract: We demonstrate the application of a subpicosecond optical parametric amplifier working at degeneracy to imaging in diffuse media. This optical parametric amplifier exhibits small-signal gains greater than 10(4), thereby acting as a high-gain ultrafast amplifying gate. We have used it to construct the image of a grid pattern hidden behind 20 mean free paths of a highly diffusing solution of latex microspheres with a spatial resolution of 200 microm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The unscattered light (ballistic component) can be selected by means of a very fast (ps) time gate. A large variety of time-gating techniques are developed based on the degree of polarization [69][70][71][72] coherent detection [73][74][75] and selection of the length of the photon paths [1,15,18,38,[76][77][78][79][80]. A systematic study of the time-gating technique has shown that it is highly sensitive with respect to spatial variations in the absorption or reduced scattering factors [38], in particular under conditions that are similar to those of biological systems of interest [38].…”
Section: Light Propagation In Turbid Mediamentioning
confidence: 99%
“…The unscattered light (ballistic component) can be selected by means of a very fast (ps) time gate. A large variety of time-gating techniques are developed based on the degree of polarization [69][70][71][72] coherent detection [73][74][75] and selection of the length of the photon paths [1,15,18,38,[76][77][78][79][80]. A systematic study of the time-gating technique has shown that it is highly sensitive with respect to spatial variations in the absorption or reduced scattering factors [38], in particular under conditions that are similar to those of biological systems of interest [38].…”
Section: Light Propagation In Turbid Mediamentioning
confidence: 99%
“…When imaging with a reflection geometry, i.e., using backscattered light, time-gating can also provide depth-resolved (time-of-flight) image information that may be used to reconstruct three-dimensional (3-D) images. Time-gating may be realized using an incoherent time-resolved detector [4], a nonlinear optical time-of-flight gate, e.g., [5], [6], and [10], or by low-coherence interferometry, e.g., [11]. It should be noted that all systems that form images through turbid media using the unscattered ballistic light are inherently limited to small scattering (tissue) depths since ballistic signals suffer exponential attenuation on passage through the scattering media.…”
Section: Introductionmentioning
confidence: 99%
“…In wide-field optical imaging schemes, this leads to a finite bandwidth of spatial frequencies that are amplified, thus limiting the achievable spatial resolution (typically on the order of tens of microns, rendering it unsuitable for applications in microscopy) [29][30][31][32]. In our experiments, we use relatively high repetition rate (resulting in relatively low-energy pulse energy) laser pulses to investigate the feasibility and potential of using the OPA for point-scanning microscopy, overcoming the previous limitations of OPA imaging in spatial resolution (wide-field mode), and in low imaging speed and/or shot-to-shot fluctuations of signals arising from the use of high energy laser pulses at low repetition rates (less than 1 kHz) [30,34]. To obtain high optical gain based on the low energy pulses, we focus the pump beam into the BBO crystal under a relatively tight focusing condition, which is determined by the optimal balance between the pump intensity (requires short focal length and tight focusing) and the acceptance angle requirements of the crystal for phase-matching (constrains the angle of the focused beam).…”
Section: Opa Gain and Snr Enhancementmentioning
confidence: 99%